2018
DOI: 10.1029/2018jc013813
|View full text |Cite
|
Sign up to set email alerts
|

Hydrography of the Central and Western Gulf of Mexico

Abstract: This study describes in detail the water masses of the Gulf of Mexico (GoM) west of 88°W based on their thermohaline properties and dissolved oxygen concentration. The existent historical information is complemented with new data from 14 cruises, Argo floats, and over one year of continuous glider monitoring. The results describe the general hydrography of the central and western GoM with focus on the difference between the water properties inside and outside Loop Current Eddies (LCEs). Caribbean Surface Water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 47 publications
5
66
0
Order By: Relevance
“…TACW originates in the tropical Atlantic Ocean and enters the Caribbean Sea through the southeastern passages ( Figure A2; Metcalf, 1976;Morrison & Nowlin, 1982). Although the origin of this oxygen depletion in this layer remains unclear, the mean current pattern suggest that TACW originates near Angola (Portela et al, 2018). We found that the core of TACW (O 2 < 120 μmol/L) was located at the 0 = 27.1 kg/m 3 isopycnal at approximately 500 dbar and had a temperature of 9.3 ± 1.2 • C and a salinity of 35.2 ± 0.2 g/kg.…”
Section: Summary Discussion and Conclusionmentioning
confidence: 99%
“…TACW originates in the tropical Atlantic Ocean and enters the Caribbean Sea through the southeastern passages ( Figure A2; Metcalf, 1976;Morrison & Nowlin, 1982). Although the origin of this oxygen depletion in this layer remains unclear, the mean current pattern suggest that TACW originates near Angola (Portela et al, 2018). We found that the core of TACW (O 2 < 120 μmol/L) was located at the 0 = 27.1 kg/m 3 isopycnal at approximately 500 dbar and had a temperature of 9.3 ± 1.2 • C and a salinity of 35.2 ± 0.2 g/kg.…”
Section: Summary Discussion and Conclusionmentioning
confidence: 99%
“…LCEs transport warm and saltier Caribbean SUW to the western GoM and play a significant role in the heat and salt budgets (Meunier et al, 2018) and modulate water mass distribution across the central and western GoM (Hamilton et al, 2018;Portela et al, 2018). A recent work by Meunier et al (2020) reports that most of the LCEs decay occurs in the central GoM through submesoscale diffusive processes at scales smaller than 0.25°and before the eddy-eddy interactions occur.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…where ρ = 1,026 kg m −3 is a mean density, C p = 4,200 J kg −1°C−1 is the specific heat capacity, θ′ and S′ are the anomalies for the temperature and salinity evaluated at each depth, respectively, and integrated over the area delimited by the edge of the LCE. For the computed AHA and ASA from glider observations, the temperature and salinity anomalies were estimated using a mean vertical profile of T/S (1993-2017) obtained from the updated climatology of the GoM reported in Portela et al (2018), whereas for the computed AHA and ASA from the model, we used a T/S climatology obtained from the 20 years NEMO simulation.…”
Section: Eddy Detectionmentioning
confidence: 99%
“…The biogeochemical cycles are partly controlled by the difference between the dark nutrient-rich waters and the upper ocean layer where the availability of light promotes the growth of phytoplankton and hence zooplankton. Figure A3 shows that the model is able to reproduce the seasonal cycle of the mixed layer in the GoM, with deepening during winter and shallowing during summer seasons (Damien et al, 2018;Portela et al, 2018). The model also shows shallower mixed layer depths during summer, and deepens during winter times respect to the Argo floats.…”
Section: Appendix a A1 Basin Scale Model Evaluationmentioning
confidence: 90%